Peri‐Implant Diseases and Biologic Complications at Implant‐Supported Fixed Dental Prostheses in Partially Edentulous Patients. Issue 5 (6th May 2020) - Tsigarida, Alexandra; Chochlidakis, Konstantinos; Fraser, David; Lampraki, Evangelia; Einarsdottir, Erna R.; Barmak, Abdul Basir; Papaspyridakos, Panos; Ercoli, Carlo
Abstract: Purpose: This is a single center, retrospective study to assess the prevalence of peri‐implant disease and biologic complications in a cohort of partially edentulous subjects in relation to selected prosthetic factors. Materials and methods: Subjects previously treated with one or more implant‐supported fixed dental prosthesis (ISFDPs) were recalled for a comprehensive examination. Clinical and radiographic records were taken and questionnaires were administered. The prevalence of implant failure, peri‐implant disease and other biologic complications were correlated with selected prosthetic, clinical and patient‐related factors using chi‐square and multiple regression analyses. Results: A convenience sample of 71 subjects with 100 prostheses supported by 222 dental implants were enrolled in the study. The mean follow‐up time after prosthesis delivery was 3.3 ± 1.5 years (range of 1‐9 years). The cumulative implant survival rate was 99.1%. Peri‐implantitis was the most frequent major biologic complication (5% of implants), while the most frequent minor biologic complication was peri‐implant mucositis (84.10% of implants). A diagnosis of peri‐implant mucositis was more likely associated with cement‐retained prostheses compared to screw‐retained prostheses (OR 6.8, 95% CI 1.1‐78.6, p = 0.045) and for short‐span prostheses (≤3 prosthetic units) (OR 2.3, 95% CI 1.1‐5.0, p = 0.034). Subject‐reported quality of life measures were high regardless of the existence of major and/or minor complications, but decreased with increasing number of minor and total biologic complications. Conclusions: Peri‐implant mucositis and other minor biologic complications were highly prevalent. The distribution of the observed complications differed based on the method of prosthesis retention and the number of prosthetic units replaced.